Management of the Nominal Public Debt Theory and Applications - Guidotti, Pablo; Calvo, Guillermo (Washington, D.C. : International Monetary Fund, 1990)
Optimal management of the public debt is explored in a context where economic policy is continuously revised because, when the public debt is non-indexed, policy-makers are tempted to use inflation in order to reduce the real value of the public debt. The model's implications are explored following two approaches. First, the effects of various exogenous disturbances are examined by means of numerical simulations. Secondly, the analysis explores-for Italy, Ireland, and the United States-if the model's implications concerning the maturity structure of government debt are consistent with actual experience.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet